Making the third ghetto. (2nd January 2021) - Smith, Preston; Bennett, Larry; Paral, Rob
ABSTRACT: Chicago's third ghetto is a cluster of "thinned out, " outlying neighborhoods that resulted from the demolition of public housing in "second ghetto" neighborhoods surrounding the central business district. The third ghetto shares some of the characteristics of the first and second ghettos—namely, the racial and economic segregation of the resident population. However, it also reveals notable, contemporary features. While the second ghetto was not deprived of public investment such as CHA developments, schools, police stations, and other public works, the third ghetto, in contrast, is a vacuum of private and public investment. It is also increasingly separated, spatially, from neighborhoods of rising prosperity. This disinvestment has created the underlying conditions for poor and working-class Black residents to feel either heavily policed or abandoned. This article traces the national and local sources of the neoliberal urban reforms of the 1990s and 2000s that ushered in a third ghetto in Chicago.